Prognosis comparison between intraoperative radiotherapy and whole-breast external beam radiotherapy for T1–2 stage breast cancer without lymph node metastasis treated with breast-conserving surgery: A case–control study after propensity score matching - Chen, Qitong; Qu, Limeng; He, Yeqing; Xu, Jiachi; Deng, Yueqiong; Zhou, Qin; Yi, Wenjun (Frontiers in Medicine, 2022)
Background: EBRT, an adjuvant to breast-conserving surgery (BCS), requires a long treatment period, is costly and is associated with numerous complications. Large sample studies with long follow-up periods are lacking regarding whether IORT, an emerging radiotherapy modality, can replace EBRT for patients with T1–2 early-stage breast cancer without lymph node metastasis treated with BCS. Methods: We identified 270,842 patients with T1-2N0M0 breast cancer from 2000 to 2018 in the Surveillance, Epidemiology and End Results (SEER) database. A total of 10992 patients were matched by propensity score matching (PSM). According to the radiotherapy method, the patients were divided into the IORT and EBRT groups. Overall survival (OS) and breast cancer-specific survival (BCSS) rates were analyzed and compared between the IORT and EBRT groups using Kaplan–Meier analysis. Bilateral P<0.05 was considered to indicate significance. Results: After PSM, the survival analysis showed no significant differences in OS or BCSS rates between the IORT and EBRT groups. In the subgroup analysis, the IORT population diagnosed from 2010-2013 (HRs = 0.675, 95% CI 0.467–0.976, P = 0.037) or T2 stage (HRs = 0.449, 95% CI 0.261–0.772, P = 0.004) had better OS rates, but in the overall population, OS and BCSS rates were better in patients with T1 stage than in patients with T2 stage (P < 0.0001), and the proportion of chemotherapy was significantly higher in T2 stage than in T1 stage. Patients with EBRT with unknown estrogen receptor had better OS rates (HRs = 3.392, 95% CI 1.368-8.407, P = 0.008). In addition, the IORT group had better BCSS rates for married (HRs = 0.403, 95% CI 0.184–0.881, P = 0.023), grade III (HRs = 0.405, 95% CI 0.173–0.952, P = 0.038), chemotherapy-receiving (HRs = 0.327, 95% CI 0.116–0.917, P = 0.034) breast cancer patients compared to the EBRT group. Conclusion: IORT results in noninferior OS and BCSS rates to those of EBRT in early-stage breast cancer patients without lymph node metastasis treated with BCS, and IORT may provide substantial benefits to patients as an effective alternative to standard treatment. This finding provides new insights into radiotherapy strategies for early-stage breast cancer.